2008
DOI: 10.1097/brs.0b013e31816960fe
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Intermittent Fluoroscopy to Detect Intravascular Injection During Transforaminal Epidural Injections

Abstract: Based on these findings, we recommend use of live fluoroscopy to observe dynamic contrast flow during transforaminal epidural steroid injections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 20 publications
1
39
2
1
Order By: Relevance
“…This incidence of simultaneous epidural and vascular injection is of clinical importance because interventionalists are more likely to miss an inadvertent vascular contrast pattern when it appears alongside the expected epidural pattern. 23 To date, no study has reported the incidence of simultaneous epidural and vascular injection in cervical transforaminal epidural injections.…”
mentioning
confidence: 99%
“…This incidence of simultaneous epidural and vascular injection is of clinical importance because interventionalists are more likely to miss an inadvertent vascular contrast pattern when it appears alongside the expected epidural pattern. 23 To date, no study has reported the incidence of simultaneous epidural and vascular injection in cervical transforaminal epidural injections.…”
mentioning
confidence: 99%
“…[5][6][7][8][9] Several authors have advocated that real-time fluoroscopy or digital subtraction angiography be used when epidural injections are performed, to maximize the detection of intravascular injections. [10][11][12] However, CT fluoroscopy (CTF) guidance, which does not use real-time fluoroscopy or DSA but does offer superior contrast resolution compared with fluoroscopy, has been increasingly used by some practitioners when performing epidural injections because it provides the benefits of cross-sectional needle localization and improved visualization of soft-tissue structures. 13,14 The ability to detect intravascular injections by using CT guidance has not been previously reported, to our knowledge.…”
Section: Abbreviationsmentioning
confidence: 99%
“…Nearly 3% of scheduled conventional scanning is delayed until operators leave the room, intravascular contrast material washes away, thereby precluding vessel identification. Intermittent fluoroscopy, if performed before and after but not during contrast material injection, also fails to show opacified vessels (52,89). In mixed injections with concurrent intra-and extravascular contrast material flow, only the extravascular contrast material remains visible, creating the false reassurance of extravascular needle placement.…”
Section: How I Do It: Spinal Injections For Pain Management Palmermentioning
confidence: 99%